Wastewater Treatment in Remote Arctic Settlements - Elena Vialkova; Ekaterina Glushchenko (Water, 2021)
The article deals with improving the sewage systems of small remote settlements in the Arctic climate to prevent industrial pollution of the environment. Preliminary monitoring of the wastewater temperature and quality was carried out. From the laboratory results of the experimental modelling, such as the coagulation, sedimentation, filtration, oxidation, and wastewater chemical precipitation, we developed a substitute for the traditional biological stage of sewage treatment with physicochemical methods. A real sewage water sample, taken for this study from a septic tank in a remote northern village, can be considered as a distinctive feature of the experiment. The best results obtained according to the scheme with the chemical precipitation of nitrogen compounds are demonstrated. In this case, the chemical oxygen demand (COD) index was reduced by 96.6%, the ammonium ions concentration by 99.5%, and the suspended solids concentration by 99.9%. A technological scheme for low-productivity wastewater treatment plants (WWTPs) in northern settlements is proposed. A comparison of the proposed scheme and the traditional schemes in terms of efficiency and cost was carried out. Further study and implementation of recommended methods of sewage treatment at existing and newly designed stations is expected to improve the effective operation of these treatment plants in arctic conditions.